Sensory- and Action-Oriented Embodiment of Neurally-Interfaced Robotic Hand Prostheses - Di Pino, Giovanni; Romano, Daniele; Spaccasassi, Chiara; Mioli, Alessandro; D’Alonzo, Marco; Sacchetti, Rinaldo; Guglielmelli, Eugenio; Zollo, Loredana; Di Lazzaro, Vincenzo; Denaro, Vincenzo; Maravita, Angelo (Frontiers in Neuroscience, 2020)
Embodiment is the percept that something not originally-belonging to the Self becomes part of the body. Feeling embodiment for a prosthesis may counteract amputees’ altered image of the body and increase prosthesis acceptability. Prosthesis embodiment has been studied longitudinally in an amputee receiving feedback through intraneural and perineural multichannel electrodes implanted in her stump. Three factors - invasive (vs non-invasive) stimulation, training and anthropomorphism - have been tested through two multisensory integration tasks: Visuo Tactile Integration (VTI) and crossing-hand effect in Temporal Order Judgement (TOJ), the former more sensible to an extension of a safe margin around the body and the latter to action-oriented remapping. Results from the amputee participant were compared with the ones from healthy controls. Testing the participant with intraneural stimulation produced an extension of peripersonal space, sign of prosthesis embodiment. One-month training extended the peripersonal space selectively on the side wearing the prostheses. More and less-anthropomorphic prostheses benefited of intraneural feedback and extended the peripersonal space. Although, the worsening of TOJ performance following arm crossing was present only wearing the more trained, despite less anthropomorphic, prosthesis, suggesting that, training was critical for our participant to achieve operative tool-like embodiment.